Association of history of adverse childhood experiences with irritable bowel syndrome (IBS) in individuals with mood disorders. (June 2020) - Rosenblat, Joshua D.; Mansur, Rodrigo B.; Brietzke, Elisa; Kennedy, Sidney H.; Carvalho, Andre F.; Lee, Yena; Subramaniapillai, Mehala; Muzina, David J.; Dale, Roman; Tamura, Jocelyn K.; Lui, Leanna M.W.; Park, Caroline; et al.
Highlights: Mood disorders are associated with an increased prevalence of irritable bowel syndrome (IBS) and history of adverse childhood experiences (ACEs) In total, 69 of the 498 mood disorder participants reported a diagnosis of IBS (13.8%) BD was associated with elevated rates of IBS compared to MDD History of childhood sexual abuse was associated with increased rates of IBS in mood disorder participants In the subgroups, history of sexual abuse was associated with an increased prevalence of IBS in BD, but not in MDD. Abstract: The objective of the current study was to assess the association between adverse childhood experiences (ACEs) and irritable bowel syndrome (IBS) in mood disorder patients. Self-report data from the International Mood Disorders Collaborative Project were cross-sectionally analyzed to compare rates of IBS in participants with confirmed diagnoses of major depressive disorder (MDD; n = 279) or bipolar disorder (BD; n = 219). Data was sub-grouped and compared based on history of ACEs. In total, 69 of the 498 participants reported a diagnosis of IBS (13.8%). BD was associated with significantly elevated rates of IBS compared to MDD (18.5% versus 10.1% respectively). After adjusting for age and sex, history of childhood sexual abuse was associated with increased rates of IBS in mood disorder participants [adjusted odds ratio (aOR) = 1.95]. In the MDD subgroup, ACEs (all categories and individual categories) were not associated with increased rates of IBS. In the BD subgroup, history of childhood sexual abuse was associated with significantly increased rates of IBS (38% versus 14%; aOR = 3.7). In summary, BD was associated with a higher prevalence of IBS compared to MDD. Additionally, history of sexual abuse was associated with an increased prevalence of IBS in BD, but not in MDD.